Efficacy and safety of Carboxitherapy associated with High Volt current in the treatment of atrophic stretch marks on glutes (Research, Society and Development, 2020)
Introduction: stretch marks are multifactorial unsightly conditions and for their treatment, resources are needed to stimulate a new process of tissue repair and regeneration. Objective: to evaluate the efficacy and safety of carboxitherapy associated with high volt current in the treatment of atrophic stretch marks. Method: This is a clinical, longitudinal, blind, prospective and comparative study, in which women with atrophic stretch marks were selected, they were evaluated and reassessed in the interval of 5 and at the end of the 10 treatment sessions. The evaluation consisted of the classification of the skin phototype using the Fitzpatrick’s Scale, analysis of the length and width of the atrophic streak, evaluation of the skin viscoelasticity with Cutometer® and photographic analysis. The treatment consisted of the application of carboxitherapy associated with the high volt current. Tukey's ANOVA and post hoc tests (p≤0.05) were performed to evaluate the results. Results: there was a decrease in the thickness of the streaks of the right gluteus between the initial assessment and 5 sessions and the initial one for 10 sessions, with respective p